Pengaruh Pembelajaran Berbasis Etnomatematika Pada Permainan Gobak Sodor Untuk Meningkatkan Pemahaman Matematis Siswa - Varadita, Zeynab; Anas, Aswar; Murtinasari, Frida (Jurnal Axioma : Jurnal Matematika dan Pembelajaran, 2025)
This research aims to determine the effect of ethnomathematics-based learning on the game Gobak Sodor to improve students' mathematical understanding. Gobak Sodor is a traditional game that is a cultural heritage from our ancestors and needs to be preserved. Gobak Sodor is a very popular traditional Indonesian game that requires good strategy, dexterity, and cooperation in a rectangular arena lined with chalk lines. This game combines elements of dexterity, strategy, and teamwork. This type of research is quasi-experimental with a quantitative approach. Class VII-A is an experimental class that uses an ethnomathematics-based learning model with the gobak sodor game, and class VII-B is a control class that uses a direct learning model. Research data was obtained through a test in the form of five questions describing mathematical understanding. Based on the results of research using an independent sample test, a significance value of 0.001 was obtained, which is smaller than 0.05. Based on this decision, H0 was rejected, which shows that there is a difference in students' mathematical understanding between the experimental class, which applies ethnomathematics-based learning with the gobak sodor game, and the control class, which uses conventional learning. These results indicate that there is a positive influence of ethnomathematics-based learning with the gobak sodor game on improving students' mathematical understanding. Keywords: Ethnomathematics, Gobak Sodor, Mathematical Understanding